Silicosis pulmonary dysfunction and respiratory symptoms in South African gold miners - Cowie, Robert Lawrence (Department of Medicine, 2014)
The purpose of this study is to examine the influence of silicosis and the occupation of gold mining on respiratory symptoms, lung function and tuberculosis in a working population of black, migrant, South African gold miners. No previous study has examined a working population of these men.